The Correlation between Knowledge Level of Young Girls and Breast Cancer Prevention in Class (X) Students at SMA Taman Siswa (TAMSIS) Pematang Siantar - Yulia Delfahedah (International Journal of Public Health Excellence (IJPHE), 2023)
Cancer breast is one reason main death consequence cancer in women. Cancer breast is malignancy the most second in women after cancer mouth uterus. Height number death consequence cancer breast caused sufferer cancer breast come to service health in the inoperable stage or advanced stage and not do BSE action so hard cured. Study this aim for knowledge teenager with prevention cancer breasts ". Relationship Level Type study this is type study type survey with share questionnaire done on the month July until september. Population in study this is high school students Park students ripening. The results of the chi square statistical test analysis were carried out for see There is relationship or No There is connection level knowledge teenager daughter with prevention cancer breast obtained mark significance (p-value) 0.02. The test results show mark significance more small than 0.05 (0.01 <0.05) then Ho is rejected and Ha is accepted It means there is significant relationship between level knowledge with prevention cancer breast class X at Taman Siswa High School Pematangsiantar 2022 year.